2001
DOI: 10.1136/vr.149.10.293
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of equine grass sickness: a literature review (1909–1999)

Abstract: The geographical spread of grass sickness between 1909 and 1999, particularly in England and Wales, is described, and the experimental investigations to identify a causal agent are summarised. The epidemiological techniques used to investigate grass sickness vary from clinical observations, to more advanced methods such as case-control studies using logistic regression analyses. Several risk factors for grass sickness have been reported consistently (age, time of year and recent movement to new pasture or prem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
57
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(62 citation statements)
references
References 26 publications
4
57
0
1
Order By: Relevance
“…Most cases of EGS occur during the spring (McCarthy et al 2001). It is known that young herbage is rich in amino acids and nitrates that are components of nonprotein nitrogen (McDonald et al 1988).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most cases of EGS occur during the spring (McCarthy et al 2001). It is known that young herbage is rich in amino acids and nitrates that are components of nonprotein nitrogen (McDonald et al 1988).…”
Section: Discussionmentioning
confidence: 99%
“…We wished to identify factors associated with EGS apart from seasonality, which has a well-documented association (reviewed by McCarthy et al 2001). Time-matching of case and control premises was intended to control for this seasonal effect.…”
Section: Study Design and Sample Size Estimatesmentioning
confidence: 99%
“…Specific types of colic are presented with higher incidence in some geographic regions; enteroliths are more frequently observed in horses in California, the Midwest, and Florida (White, 1990), grass sickness is diagnosed in Europe (McCarthy et al, 2001;Protopappas et al, 2012), while sand colic impactions are reported in horses that graze on sandy soils or are forced to eat off ground. Furthermore, dietary management consisting large amount of grain (White, 2006) and transport are thought to be associated with increased risk of colic (Hillyer et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…According to literature, a number of factors associated with increased risk of colic have been proposed, including sex, age, breed, management, increasing exercise, transport, feeding practices and parasite control (Cohen et al, 1996;Cohen et al, 1999;Archer et al,2006). The association of colic with weather-related factors has been proposed by some authors; however no statistical proof has been reported to substantiate this theory (Cohen, 1997;McCarthy et al, 2001;Gonçalves et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…This suggested the introduction of a novel infectious disease. 70 By 1922, cases of equine grass sickness (EGS) were seen in horses in the Salisbury Plain area of England. 67 EGS remains endemic in Scotland, England, and Wales and has also been reported from continental Europe, the Falkland islands, and Colombia with isolated cases in Australia and the United States.…”
Section: History and Epidemiologymentioning
confidence: 99%